2008
DOI: 10.1097/bpb.0b013e328311d3e9
|View full text |Cite
|
Sign up to set email alerts
|

Congenital agenesis of pubic bones: a case report

Abstract: Congenital absence of bilateral pubic bones is extremely uncommon. A 2-year-old boy presented with a history of intoeing at our outpatient clinic. The testes were found located at the inguinal canal on ultrasonography. A pelvic radiograph and a spiral computed tomography scan of the pelvis with three-dimensional reconstruction revealed the absence of both pubic bones. In conclusion, we report that the absence of the pubic bones, either as an isolated finding or associated with undescended testes, is peculiar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…No operative intervention was reported in these cases. Other examples of unique pelvic dysmorphism reported in the literature include hypoplasia of parts of the pelvic ring, most commonly involving the pubis as with the previously noted case reports [6][7][8]. No common genetic risk factors were noted in these cases.…”
Section: Discussionmentioning
confidence: 71%
“…No operative intervention was reported in these cases. Other examples of unique pelvic dysmorphism reported in the literature include hypoplasia of parts of the pelvic ring, most commonly involving the pubis as with the previously noted case reports [6][7][8]. No common genetic risk factors were noted in these cases.…”
Section: Discussionmentioning
confidence: 71%
“…Cases with phenotypes resembling that of our patient have been previously described. Several patients with unilateral or bilateral absence of the pubic ramus associated with dislocation of the hip [Guilleminot et al, Slullitel, ; Saber, ; Yusuf and Negash, ] or with genitourinary anomalies such as hypospadias and cryptorchidism [Sarban et al, ], cryptorchidism [Yildiz et al, ], and the absence of the uterus [Bashyal et al, ] have been published. The more extensive and wide‐spread anomalies in the present patient are clearly different from the above‐mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Like our study, Yildiz et al showed a rare entity that undescended testes with agenesis of pubic rami. 6 …”
Section: Discussionmentioning
confidence: 99%